Evaluasi Dan Perbaikan Rancangan Antarmuka Pengguna Pada Piknik Nusantara Menggunakan Metode Design Thinking - Bagus Taufik Wicaksono; Hanifah Muslimah Az-Zahra; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Piknik Nusantara is a company engaged in organizing Event Organizers. Piknik Nusantara wants a website-based platform to assist in managing travel stock data collection for traveling packages that can help purchase and manage travel data flexibly and efficiently. Based on these problems, the researcher provides a solution by designing the user experience of the Piknik Nusantara website- based system that creates the final result in the form of a high-fidelity prototype. The system design will make it easier for consumers to order vacation travel transactions, this design process uses design thinking, which has five stages, namely empathize, define, ideate, prototype, and test. Tests in this study will assess the aspects of learnability, efficiency, and satisfaction by using usability testing with task scenarios and system usability scale (SUS). Based on the test results for the general user system, it is obtained a value of "82.5" which is included in the characteristics of the "high acceptability" level, the grade scale is the same as "B", and the adjective rating is classified as "almost good". For the system administrator, the score "85" is included in the characteristics of the "high acceptability" level, the grade scale is the same as "B", and the adjective rating is classified as "excellent".